Comparative study on the readiness of Mobile Learning Application in Learning - Ahmad, W.F.W. (Institute of Electrical and Electronics Engineers Inc., 2021)
Mobile application has been widely used as a learning aid in education. It could be the best learning service for adult's learner. The benefits of mobile app include increasing learning accessibility, reducing learning costs, promoting lifelong learning and many others. However, early studies have reported that there are challenges in promoting mobile learning due to the readiness of the users. Therefore, this project aims to conduct a comparative study by examining the students' readiness towards the use of mobile application in learning. The investigation will focus on 100 students from UTP, Malaysia and Uhamka, Indonesia. Questionnaire has been distributed using random sampling method. The results have shown that there was no significant difference between the two samples, hence, it can be concluded that both students from universities are ready for the use of mobile learning. Â© 2021 IEEE.